A panel co-integration analysis of industrial and services sectors' agglomeration in the European Union - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2012)
This study empirically investigates the relevance of Traditional Trade Theory, New Trade Theory and New Economic Geography in explaining industrial and services sectors' agglomeration in the European Union. Therefore, new dynamic panel data estimation techniques will be employed. Static panel data analysis reveals that assumptions of New Trade Theory and New Economic Geography can explain industrial concentration in the EU best. Results from dynamic panel OLS show that intermediate goods' intensity and therewith New Economic Geography's assumptions are important in explaining both industrial and services sectors' agglomeration. Several non-stationarity and co-integration relationships can be detected. Further, decomposition of effects across and within sectors is provided. Scale economies are only important for across industries' variation in agglomeration, not within. For services sectors' agglomeration results show that intermediate goods intensity matters only for within and not across industries' variation in agglomeration. Further evidence for intrasectoral trade explaining equalizing economic structures for services sectors is given.
Keywords: C22; F14; R12; 330; panel co-integration; agglomeration; industries; services